Kualitas Nutrisi dan Uji Daya Cerna Kulit Singkong Hasil Fermentasi Beberapa Inokulan - Kaspul Anwar; Danang Biyatmoko; Habibah Habibah (www.ulm.ac.id, 2014)
The objective of this research was to study the effect of fermentation using different inoculans onthe quality of nutrient and digestibility of cassava peels, namely: crude protein (CP), metabolismenergy (ME), dry matter digestibility (DMD), and retention of nitrogen of male Alabio duck on 8weeks of age. This research used completely randomized design with four treatments and fivereplications. Treatment of this research was difference of inoculans as fermentation starter, i.e.P0 (non fermented cassava peels as a control), P1 (fermentation with EM4 for animal feed), P2(fermentation with tapai yeast), and P3 (fermentation with Starbio). Results of this researchshowed that fermentation was significantly affect on CP and ME (P<0.05), and could increaseDMD and nitrogen retention of cassava peels for male Alabio duck on 8 weeks of age. Inconclusion, fermentation using tapai yeast (P2) is the best inoculant in increasing nutrient qualityof fermented-cassava peels those were 9.36% of CP and 2,790.40 kkal/kg of ME. The bestinoculant for increasing DMD of cassava peels was Starbio (68.27%), whereas tapai yeast wasthe best inoculant for increasing nitrogen digestibility (80.53%)